The Impact of Discount Frame and Type of Product on Purchase Intention - Reliano Aldoreno; Chairy Chairy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2021)
In this modern era, shifting the type of product from physical to digital has been popular. As an example, a textbook that been used by students in university may be acquired in the digital form which is an e-book. Marketing promotion is not only for a textbook, yet e-book should be treated the same. Online seller in Indonesia does promotion which is price discount to attract customer. Accordingly, there are two types of price discount frames which are % form or absolute form. Both may attract customers differently. Therefore this research aimed to find the impact of discount frame and type of product on customer purchase intention. The sample number is 92 students who take management Master's Degree at Tarumanagara University and the object of this research is purchase intention. This research used experimental design 2x2 factorial. SPSS program is used to do an ANOVA analysis. The first independent variable is the discount frame with two sub-factorials which are % discount and Rp discount. The second independent variable is the type of product with two sub-factors which are textbooks and e-book. The result showed that type of product has a significant effect on customer purchase intention. There is no significant effect of the discount frame on purchase intention. The research result also showed that type of product does not moderate the relationship between discount frame and customer purchase intention.  Pada zaman modern saat ini, perkembang bentuk produk dari bentuk fisik menjadi digital semakin banyak. Sebagai contoh, textbook yang dapat diakses digital dan dikenal dengan istilah e-book. Promosi marketing tidak hanya berlaku untuk textbook, melainkan e-book juga. Penjual online di Indonesia melakukan promosi yaitu diskon harga untuk menarik perhatian konsumen. Terdapat dua jenis discount frame yaitu diskon % atau potongan harga dimana dapat menarik perhatian konsumen secara berbeda. Maka dari itu, penelitian ini bertujuan untuk mengetahui pengaruh discount frame dan type of product terhadap minat beli konsumen. Jumlah sampel adalah 92 siswa yang mengambil gelar Magister Manajemen di Universitas Tarumanagara dan objeknya adalah minat beli konsumen. Penelitian ini menggunakan desain faktorial 2x2. Program SPSS digunakan untuk melakukan analisis ANOVA. Variabel independen pertama adalah discount frame dengan dua sub-faktorial yaitu diskon % dan diskon Rupiah. Variabel independen kedua adalah type of product dengan dua sub-faktor yaitu buku textbook dan e-book. Hasil analisa menunjukkan bahwa type of product memiliki efek yang siginifikan terhadap purchase intention. Tidak ada pengaruh yang signifikan antara discount frame dan purchase intention. Hasil analisa juga menunjukan bahwa type of product tidak memoderasi hubungan antara discount frame dan purchase intention.